TINJAUAN PELAKSANAAN PROGRAM BEHAVIOR BASED SAFETY (BBS) DI FILLING SHED AND GATE KEEPER TERMINAL BBM MEDAN GROUP PT. PERTAMINA (PERSERO) REGION I SUMBAGUT LABUHAN DELI-BELAWAN MEDAN - khairul anwar tambunan (Lingkungan dan Kesehatan Kerja, 2014)
AbstractBehavior Based Safety Program plays an important role in reducing the incidence ofoccupational accidents and prevent health problems from work, Especially in a job that uses ahigh-temperature machine, has the risk of fire, and chemicals in several stages of production.Implementation of behavior based safety program focused early to know unsafe behavior beforeinjuries occur and changes the behavior of a safer workplace.This research uses descriptive research with quantitative approach that aims to describe theapplication of behavior-based safety program in gas station terminal of Medan. Sample in thisstudy is 14 people and taken by total sampling at the Filling Shed and Gate Keeper. Data werecollected by direct observation and interviews with workers using a questionnaire containingstatements about the behavior-based safety program.The results showed that the implementation of Behavior Based Safety at the Filling Shed andGate Keeper in gas station terminal of Medan, Group of PT. Pertamina (Persero) Region ILabuhan Deli-Belawan North Sumatra is in good category and equal to 92.9%.Based on the research results, the expected in gas station terminal PT.Pertamina is directapproaches such as have appealed to work safely and training concerning safety issues especiallyregarding the Behavior Based Safety.Keywords: Behavior Based Safety , Filling shed and Gate Keeper, PT. Pertamina, Labuhan Deli